5 - MINUTE ADA TWIST, SCIENTIST STORIES - Meyer, Gabrielle (New York : Abram Books for Young Readers, 2022)
"A charming storybook collection of sweet tales based on the Netflix series starring Ada Twist--perfect for read-alouds or bedtime! Revisit some of your favorite episodes of the Netflix series, in print for the first time, with this gifty storybook collection. Each of the 12 stories retells a beloved episode from the show, making it perfect for group read-alouds or when it's time to settle down for bed"--Amazon.com.
Keywords: Scientist stories; Scientists -- Juvenile fiction; Science Experiments -- Popular works; Science -- Experiments -- Juvenile humor